2020
DOI: 10.1177/1687814019897510
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy effects on nanoliquids film flow through a porous medium with gyrotactic microorganisms and cubic autocatalysis chemical reaction

Abstract: This article is based on the mathematical model constructed to analyze the simultaneous flow and heat transfer of two nanoliquids (Casson and Williamson) in the presence of gyrotactic microorganisms and cubic autocatalysis chemical reaction through a porous medium under the potentiality of buoyancy forces. Heterogeneous reaction existing on the surface is described by isothermal cubic autocatalytic chemical reaction, whereas homogeneous reaction is taking place at far field described by first-order kinetics. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Maleque 27 investigated activation energy accompanying both type of reactions of heating absorbing and evolving in the movement and heating transportation for which numerical solution was obtained through RKF with the collaboration of other procedure along with NS iteration procedure. Since activation energy is related to heating and saturation transferring so the heating and saturation transferring studies may be consulted in the references [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…Maleque 27 investigated activation energy accompanying both type of reactions of heating absorbing and evolving in the movement and heating transportation for which numerical solution was obtained through RKF with the collaboration of other procedure along with NS iteration procedure. Since activation energy is related to heating and saturation transferring so the heating and saturation transferring studies may be consulted in the references [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…′ Illustration of different mathematical letters and notations used in Eqs. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) are given in Table 1. Substituting the values from Eq.…”
Section: Methodsmentioning
confidence: 99%
“…They applied the finite difference method and observed that enhanced heat transfer exist by placing the heater in lower half of the inner wall. Zuhra et al 6 presented the work on gravity driven simultaneous flow of Casson and Williamson nanofluids and heat transfer with homogeneous-heterogeneous chemical reactions. Sankar et al 7 attempted numerically the natural convection heat transfer in a cylindrical annular cavity with discrete heat sources on the inner wall whose purpose is to cool the chips in an effective way to prevent overheating and hot spots.…”
mentioning
confidence: 99%
“…Zuhra et al. [ 14 ] constructed a mathematical model to investigate the flow and heat transportation of two nanoliquids (Williamson and Casson) under the influence of autocatalysis chemical reaction and gyrotactic microbes through a porous media along a vertical solid surface. The similarity transformation was utilized to solve the flow model equations and then the acquired coupled differential equations were simplified by employing the Homotopy Analysis Method (HAM).…”
Section: Introductionmentioning
confidence: 99%